PERAN LEMBAGA ADAT MELAYU RIAU KABUPATEN KUANTAN SINGINGI TERHADAP PENCEGAHAN TINDAK PIDANA PENAMBANGAN EMAS TANPA IZIN (PETI) DI KABUPATEN SINGINGI - Rahma Riyanti; Erdianto Erdianto; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The living environment is a spatial unit with all objects, forces, conditions, and living things including humans and their behavior will affect the continuity of life and the welfare of humans and other creatures. The environment can be defined as all objects and conditions including humans and their actions that are contained in the space where humans are located and affect the life and welfare of humans and other living bodies. To protect the environment and control acts of environmental pollution and destruction, environmental law enforcement efforts are needed. Enforcement of environmental law can be interpreted as the use or application of instruments and sanctions in the fields of administrative law, criminal law and civil law with the aim of forcing the subject of the law to comply with environmental laws and regulations. In Article 67 of Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management, it is explained that every person is obliged to maintain the preservation of environmental functions and control environmental pollution and damage. This type of research can be classified into sociological juridical research where the research tests the effectiveness of the current law. This sociological legal research is a type of research that is viewed from the purpose of legal research. Sociological or empirical legal research consists of legal identification (unwritten) and research on the effectiveness of the law. From the research results, there are 2 main problems that can be concluded. First, the implementation of criminal acts and prosecution against the perpetrators of gold mining without a permit in the police unit of the Kantan Singi resort includes preventive and repressive measures. Preventive and repressive preventive measures have not been maximally implemented. It can be seen that there are still unlicensed gold mining that has not been processed by law enforcement officers at the Kuantan Singi Resort Police.Keywords: Mining-Environment-Pollution-Destructio